An overview on exploration and environmental impact of unconventional gas sources and treatment options for produced water. (15th September 2017) - Silva, Tânia L.S.; Morales-Torres, Sergio; Castro-Silva, Sérgio; Figueiredo, José L.; Silva, Adrián M.T.
Abstract: Rising global energy demands associated to unbalanced allocation of water resources highlight the importance of water management solutions for the gas industry. Advanced drilling, completion and stimulation techniques for gas extraction, allow more economical access to unconventional gas reserves. This stimulated a shale gas revolution, besides tight gas and coalbed methane, also causing escalating water handling challenges in order to avoid a major impact on the environment. Hydraulic fracturing allied to horizontal drilling is gaining higher relevance in the exploration of unconventional gas reserves, but a large amount of wastewater (known as "produced water") is generated. Its variable chemical composition and flow rates, together with more severe regulations and public concern, have promoted the development of solutions for the treatment and reuse of such produced water. This work intends to provide an overview on the exploration and subsequent environmental implications of unconventional gas sources, as well as the technologies for treatment of produced water, describing the main results and drawbacks, together with some cost estimates. In particular, the growing volumes of produced water from shale gas plays are creating an interesting market opportunity for water technology and service providers. Membrane-based technologies (membrane distillation, forward osmosis, membrane bioreactors and pervaporation) and advanced oxidation processes (ozonation, Fenton, photocatalysis) are claimed to be adequate treatment solutions. Graphical abstract: Highlights: Unconventional gas represents 40% of the world's recoverable natural gas. Exploration and environmental implications of unconventional gas are discussed. Large amounts of wastewater, known as "produced water", are generated. Water management and alternative treatment technologies are reviewed. Treatment and reuse of "produced water" represent an interesting market opportunity.